LIPYAKSARA: THE CREATION OF THEATER ART USING ARTAUD'S CRUEL THEATER STYLE - Dharma, A. M. Surya Chintya (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: Lipyaksara is the name of a book owned by Calonarang. Calonarang herself is a powerful and magical woman. The contents of the Calonarang book contain mantras about good and evil. The Lipyaksara book created a conflict between Calonarang and King Airlangga's party in order to control the book. Creating war and Calonarang lost the battle. The story was realized into a theater performance with the same title as the book, Lipyaksara. The novel by Cok Sawitri entitled